A Novel Mohs Precision Tool. Issue 2 (February 2018) - Kanevsky, Jonathan; Safran, Tyler; Viezel-Mathieu, Alex; Hemmings, Kurt; Khanna, Manish
Abstract : BACKGROUND: Effective treatment by Mohs micrographic surgery requires preparation of high-quality slides. OBJECTIVE: To examine a novel tissue alignment device designed to address variability in tissue processing because of excessive sample trimming. MATERIALS AND METHODS: A device was designed to account for angular errors and unparalleled tissue embedding. A retrospective chart review was performed both with and without the use of the device over the course of a 4-year period (2012–2015). RESULTS: Between January 1, 2012, and June 10, 2014, before device implementation, mean number of stages per case was 1.65 ( n = 3, 680) and mean number of surgeries per day was 6.34 ( n = 640). Between June 11, 2014, and October 02, 2015, with device implemented, the average number of stages per case between decreased to 1.58 ( n = 2, 562) and the number of daily surgeries increased to 7.05 ( n = 358). This represents a significant decrease in number of stages per case by 0.07 stages (95% CI: −0.01 to −0.13, p = .02), as well as an increase in the number of cases per day by 0.71 cases (95% CI: 0.12–1.3, p < .01). CONCLUSION: Slide preparation using the novel alignment device may result in less tissue waste and more cases being performed daily.